Translation and language education pedagogic approaches explored - Laviosa, Sara (London Routledge, 2014)
"The revival of translation as a means of learning and teaching a foreign language and as a skill in its own right is becoming a reality in undergraduate as in postgraduate degree programmes. The main reasons for this remarkable comeback lie in recent changes in Applied Linguistics such as the support for the use of the L1 in foreign language learning, the development of the ecological approach to the study of language and second language acquisition as well as an interest in glossodiversity and semiodiversity in our increasingly globalized world. This book examines the ebb and flow of the role of pedagogic translation starting with the Grammar Translation Method and concluding with the more recent ecological approaches to Foreign Language Education. Drawing on the convergence between the view of language and translation embraced by ecologically-oriented educationalists such as Claire Kramsch (2009) and the theoretical underpinnings of the holistic approach to translating culture proposed by Maria Tymoczko (2007), this volume puts forward a holistic pedagogy that harmonizes the teaching of language and translation in the same learning environment. The goal is to form multilingual subjects with deep translingual and transcultural competence. This entails the ability to critically reflect on the world and ourselves through the eyes of another language and culture."--Provided by publisher.
Includes bibliographical references (pages 164-171) and index.
Keywords: Translating and interpreting -- Study and teaching; Translating and interpreting -- Vocational guidance; Language and languages -- Study and teaching